Optical properties and band structure of semiconductors - Greenaway, David L.; Harbeke, Gunther (International series of monographs in the science of the solid state, 1968)
Optical Properties and Band Structure of Semiconductors, Volume 1 presents the experimental studies of the fundamental energy band structure of semiconductors and insulators. This book provides detailed information of the available measurement methods and results for a large number of both cubic and non-cubic materials. Comprised of 10 chapters, this volume begins with an overview of the fundamental band structure of semiconductors. This text then discusses the instrumentation and methods available for the measurement of absorption coefficient, absolute reflection coefficient, and other optica.